2009
DOI: 10.1007/s10681-009-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Contrastant banana accessions for resistance to the burrowing nematode, based on molecular markers RAPD

Abstract: This work aimed to proceed molecular characterization of seven banana accessions (Borneo, Grand Naine, 1304-06, 4249-05, 0337-02, 0323-03 and 4279-06) resistance to the nematode Radopholus similis. These accessions were selected taking in account the reproduction factor (RF) among 26 banana genotypes from a working collection belonging to Embrapa Mandioca e Fruticultura Tropical.The genomic DNA of the seven accessions was extracted, and 36 decamere primers had been used to obtain RAPD markers. The resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This is proposed that DNA bands probably characterize repetitive sequences [23,40]. The variation and or polymorphism in repetitive DNA sequences has normally been detected during plant tissue culture studies [57,65]. The tissue culture stress may give rise to deviations at privileged sites, like repetitive DNA, thereby stimulating transposons.…”
Section: Rapd Analysismentioning
confidence: 99%
“…This is proposed that DNA bands probably characterize repetitive sequences [23,40]. The variation and or polymorphism in repetitive DNA sequences has normally been detected during plant tissue culture studies [57,65]. The tissue culture stress may give rise to deviations at privileged sites, like repetitive DNA, thereby stimulating transposons.…”
Section: Rapd Analysismentioning
confidence: 99%
“…Nematode management in banana plantations relies mainly on the use of chemical nematicides. However, in addition to being expensive, nematicides can cause environmental degradation, have the potential to leave residues on fruits, contaminate groundwater, and affect non-target organisms, and pose a risk of toxicity to applicators [27][28][29]. Cultural control measures, such as rhizome cutting followed by hot water treatment, and the use of healthy shoots or clean planting material, such as those from tissue culture, offer only temporary nematode management, as fields are usually reinfested [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…have indicated direct correlations between the number of burrowing nematodes in banana roots and root damage (FALLAS et al, 1995;MARIN et al, 1999;MOENS, 2004;SANTOS et al, 2013). Therefore, quantifying R. similis population levels in roots may be used to determine differences in aggressiveness among populations.…”
Section: Introductionmentioning
confidence: 99%
“…Dochez et al (2009) assessed the progeny resulting from a cross between the diploid hybrids TMB2 x 6142-1 and TMB2 x 8075-7 and found that two dominant genes controlled resistance, named A and B, both with additive and interactive effects, by which the recessive bb suppresses the dominant A. Moreover, genetic differences among R. similis populations in Musa accessions have been detected by DNA markers and phenotype evaluations (COSTA et al, 2008;SANTOS et al, 2010). Melo and Santos (1999) tested a modified version of Griffing model IV (GRIFFING, 1956) that provides simplified information on horizontal and vertical resistance on the host and pathogen virulence and aggressiveness.…”
Section: Introductionmentioning
confidence: 99%